Framing overtourism: a critical news media analysis. Issue 17 (1st September 2020) - Phi, Giang Thi
ABSTRACT: To better comprehend how the news media frames modern overtourism, content analysis was conducted on 202 news articles. Results suggest that root causes of overtourism are largely overlooked and the focus is on reporting tourist numbers and impacts on local. The growth agenda continues to be promoted in the backdrop of overtourism news, while responsibilities to mitigate negative impacts are attributed to cities, communities and tourists. There is a need to explore responsibilities of diverse tourism actors in addressing overtourism, along with discussions on alternatives to the pro-growth paradigm and the industrial work-home-travel model that fuel modern mass tourism.